Computer control of batch process plant (software and hardware development) / Abd. Shukor Kelinng - Kelinng, Abd. Shukor (1996)
This project looks up mostly in which more enhanced computer control can be provided in the batch process plant. The competitive pressure in batch process plant production and difficulties in planning and control all call for improved design of batch process plants and provide an incentive for application of computer-aided methods. Personal computer is being used in data acquisition and control boards. The plant is simulated by using stepper motor where the motion or rotation of the motor can be controlled by the computer. The interfacing boards are inserted into the computer bus slots and linked with the selected plant which is simulate by using stepping motor.